Genome-wide identification, expression and functional analysis of Populus xylogen-like genes. (October 2019) - Wang, Caili; Chen, Lincai; Yang, Heyu; Yang, Shaohui; Wang, Jiehua
Highlights: Thirty-one xylogen-like ( XYLP ) genes in Populus trichocarpa genome are expressed in close association with xylem formation process. PtXYLP1 was preferentially expressed in cotyledon and vascular tissues of hypocotyls and roots; while PtXYLP2 was mainly located in the guard cells and leaf midvein. PtXYLP1 but not PtXYLP2 overexpression in Arabidosis affected the patterning and continuity of veins in cotyledons. PtXYLP1 overexpression repressed the expression level of genes critical for embryonic venation development. Xylogen is likely to be involved in the maintenance of vascular strand continuity in cotyledons at the early developmental stage. Abstract: As an extracellular arabinogalactan protein (AGP) containing a non-specific lipid transfer protein (nsLTP) domain, xylogen mediates the local intercellular communication required for tracheary element (TE) differentiation in Zinnia cell culture. Although XYLP (xylogen-like protein) gene families have been reported in Arabidopsis and rice, no comprehensive analysis has been performed in woody plants. In this work, 31 XYLP genes in five phylogenetic groups were identified from Populus trichocarpa genome and a comprehensive bioinformatic analysis including gene and protein structures, chromosomal locations and duplication events were conducted. In-silico data and qRT-PCR results indicated that PtXYLP1 is predominantly expressed in poplar apex, young leaves and roots, while PtXYLP2 is uniformly expressed across a variety of tissues with a low abundance. Analysis on PtXYLP1pro:GUS and PtXYLP2pro:GUS in Arabidopsis revealed their differential expression patterns during seed germination and specific inductions by exogenously applied phytohormones including auxin, cytokinin and GA. When overexpressed in Arabidopsis, PtXYLP1 but not PtXYLP2 resulted in cotyledons with defective venation patterns and interrupted secondary (2°) vein loops, which phenotype was underpinned by the down-regulation of genes indispensably required by embryonic venation development at procambium and/or vessel level.